Jehovah’s Witnesses and Bioethics, Right to Treatment and Religious Freedom (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
Jehovah’s Witnesses’ refusal of blood transfusions has crossed legal and scientific culture for several decades, leaving an indelible mark. The analysis starts from the religious reasons for such a choice and examines the propulsive stimulus offered to the judiciary to cover the regulatory gap with its decisions, to the legislature to pass the law on informed consent, and to physicians driven to develop new techniques and to apply bloodless medicine more and more widely. The article focuses on the particular use of advance directives in a pro-life sense, the important results achieved and the difficulties that still exist in enforcing patients’ rights.